92.5k views
3 votes
For f(x) = 4x +1 and g(x) = x2 - 5, find (g/f) (x).

User Bubly
by
5.5k points

1 Answer

4 votes

Answer:


\left(g/f\right)\left(x\right)=(x)/(4)-(1)/(16)-(79)/(16\left(4x+1\right))

Explanation:


f(x)=4x+1


g\left(x\right)=x^2\:-\:5

As

(g/f)(x) = g(x) / f(x)


=\:(x^2\:-\:5)/(4x+1)\:\:\:\:\:\:


=(x)/(4)+(-(x)/(4)-5)/(4x+1)


=(x)/(4)-(1)/(16)+(-(79)/(16))/(4x+1)


=(x)/(4)-(1)/(16)-(79)/(16\left(4x+1\right))

Therefore,


\left(g/f\right)\left(x\right)=(x)/(4)-(1)/(16)-(79)/(16\left(4x+1\right))

User Peter Meinl
by
5.9k points